Performance of a pharmaceutical services regionalization strategy policy in Minas Gerais, Brazil: Pre-post analysis from ERAF project - Luz, Tatiana Chama Borges; Castro, Ana Karine Sarvel de; Marques, Isabela Cristina; Cota, Betania Barros; Alves, Jèssica de Castro; Law, Michael Robert (Frontiers in Pharmacology, 2022)
Background: In 2016, the Brazilian State of Minas Gerais (~20 million people), implemented the ERAF policy (‘Regionalization Strategy of Pharmaceutical Services’) in an effort to improve medicines procurement and distribution within primary care. We evaluated the impact of the policy on three main goals: price reductions, volume increases, and expansion of therapeutic options. Methods: We analysed procurement data from the Integrated System of Management of Pharmaceutical Services database in 2012 and 2018. We estimated the volume, drug mix and expenditure indicators for all major therapeutic classes, and for cardiovascular and nervous system drugs specifically. We evaluated the expenditure drivers using decomposition analyses. Results: Overall, expenditure increased by 14.5%, drug mix almost doubled, while volume decreased by a third. Cardiovascular and neurological system drugs followed similar patterns. Decomposition analyses showed that prices and drug mix had positive effects while volume had negative effects, resulting in an overall increase in expenditure. Conclusion: Our findings suggest that ERAF policy cannot be considered effective as it has not fulfilled its intended purposes so far. Strategies to address the identified problems and to build a platform for a more sustainable long-lasting policy should be put in place by the government.